Teaching Clinical Radiology - Campodónico, Esteban (1923)
As is well known, since the radiological science emerged, his study at the School, has been an integral part of medical physics, which appeared to be a dependent part, due to both lineage and the media that it was necessary to bring into play for the production of X-rays.